2018
DOI: 10.1007/s00246-018-1973-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a New Echocardiographic Index to Predict Need for Trans-annular Patch in Tetralogy of Fallot

Abstract: The long-term outcome after repair of tetralogy of Fallot (TOF) is critically dependent pulmonary valve competence that is compromised by trans-annular patch (TAP). We compared a new echocardiographic index [pulmonary annulus index (PAI)] to conventional methods of predicting need for TAP in infants undergoing TOF repair. Consecutive infants undergoing TOF repair were prospectively studied. Pre-operative aortic and pulmonary annuli and main pulmonary artery (MPA) diameters were measured and z scores determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In this cohort, 130 (45.4%) patients underwent repair without TAP augmentation, which is similar to or even better than the results reported by other centers (18)(19)(20). However, it is thought that the placement of the TAP often results in relatively delayed postoperative recovery after surgical repair (17).…”
Section: Treatment Management and Early Outcomes Of Tof Patientssupporting
confidence: 83%
“…In this cohort, 130 (45.4%) patients underwent repair without TAP augmentation, which is similar to or even better than the results reported by other centers (18)(19)(20). However, it is thought that the placement of the TAP often results in relatively delayed postoperative recovery after surgical repair (17).…”
Section: Treatment Management and Early Outcomes Of Tof Patientssupporting
confidence: 83%
“…In some recent studies, alternative measurement methods have been proposed that can be used instead of the pulmonary annulus Z-score. Kasturi et al suggested the use of "pulmonary annulus index," calculated indirectly by using the pulmonary and aortic annulus diameters and which expresses the proportion of observed and expected pulmonary annulus diameters along with the pulmonary annulus Z-scores (15) . Choi et al stated that the ratio of pulmonary-to aortic annulus diameter and descending aorta diameter can be used for this purpose (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Z score calculations of the pulmonary valve ring and active artery were based on the literature published in 2017 17 . GA ratio refers to the ratio between pulmonary and aortic annulus, whereas PAI 18 refers to the concept that in a normal heart, the conical diaphragm divides the arterial trunk (common outlet artery) into two equal left and right ventricular outflow passages. Correspondingly, the size of the pulmonary artery and aortic annulus is almost equal.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, Choi et al 17 proposed that the ratio between the pulmonary annulus and aortic annulus should be used to predict whether TAP is needed in TOF correction. In 2019, Kasturi et al 18 proposed that TAP could be predicted from the pulmonary annulus index (PAI). In 2020, Zhao et al 19 used phylum‐to‐aortic valve annulus cross‐sectional area ratio (PAAI) to predict TAP.…”
Section: Introductionmentioning
confidence: 99%